ON THE COMPUTATION OF FIXED POINTS FOR RANDOM OPERATOR EQUATIONS - Argyros, I. K.; Hilout, S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
We approximate fixed points of random operator equation on a complete probability space using Newton’s method. Error bounds on the distances involved and some applications are also provided in this study.